The Development of a Test Stand for Electric Fuel-Cell Turbocharger Integrity Testing—Part 2: Results - Georgios Karakasis; Sebastian Kunze; Georgios Iosifidis; Anestis Kalfas (Engineering Proceedings, 2025)
This paper presents the results of a testbench regarding the effects of liquid water content in the turbine stage of a fuel-cell charging system. The testbench simulates the exhaust conditions of a PEM fuel cell to evaluate erosion potential in a single-stage aluminum turbine and assess the effectiveness of liquid water separators. Key factors such as changes in turbine geometry and performance were analyzed. Erosion influence to low-cycle fatigue potential is assessed via eigenfrequency measurements. Turbine stage-efficiency measurements are used to calculate the thermodynamic impact of erosion. Three-dimensional scanning, eigenfrequency measurements, and performance map calculations showed a 5.4% crater-to-blade thickness change, <0.6% frequency shift, and finally, a <0.1% change in efficiency, indicating that erosion remained at the incubation stage. Centrifugal separators showed superior performance compared to mesh types. The hardest aspect of the work was to minimize measurement error.